Hubungan Pengetahuan tentang Tablet Tambah Darah dengan Sikap dan Tindakan Konsumsi Pada Mahasiswi Farmasi Poltekkes Kemenkes Aceh - Burdah Burdah; Alfia Amlisa; Ernita Silviana; Amelia Sari; Rima Hayati (Jurnal Pharmacopoeia, 2026)
Anemia is a common nutritional problem among young women and is caused by inadequate intake of essential nutrients, particularly iron. In Indonesia, the prevalence of anemia among women remains relatively high and poses a public health concern, especially among adolescents and young adults. Iron supplementation tablets are one of the government’s strategies to prevent anemia; however, adherence to their consumption remains low. This study aimed to examine the relationship between knowledge of iron supplementation tablets and attitudes and consumption actions among female Pharmacy students at Poltekkes Kemenkes Aceh. This study was an observational study with a cross-sectional design. The study population consisted of female students enrolled in the Department of Pharmacy at Poltekkes Kemenkes Aceh. A total of 78 respondents were selected using a simple random sampling technique. Data were collected using structured questionnaires and analyzed using Fisher’s Exact Test. The results showed a significant relationship between knowledge of iron supplementation tablets and attitudes toward consumption (p = 0.001; p < 0.05). However, no significant relationship was found between knowledge and consumption actions (p = 0.366; p > 0.05). These findings suggest that although knowledge influences attitudes, actual consumption actions are affected by factors beyond knowledge alone.In conclusion, knowledge of iron supplementation tablets is related to attitudes but is not related to consumption actions among female Pharmacy students at Poltekkes Kemenkes Aceh. Strengthening supportive factors is necessary to improve adherence to iron supplementation.